Radiator for Wireless Charging Application Based on Electromagnetic Coupling Resonant - Ni Wayan Dessy Eka Rahayu; Achmad Munir (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
This paper presents the design and characterizationof radiator for wireless charging application. The radiator isdesigned based on electromagnetic coupling resonant using amicrostrip patch in spiral shape to work at operating frequencyaround 10MHz with the dimension of patch deployment of 50mm× 60mm. The design process includes characterizations of variedpatch length and of gap separation between 2 stacked radiators toachieve the optimum performance. After obtaining the optimumdesign, the radiator is deployed on a side of FR4 Epoxy dielectricsubstrate with the thickness of 0.8mm, whilst the other sideis applied for a groundplane. The realized radiator is thenmeasured experimentally to obtain its characteristic responsesto be compared with the design results. From numerical characterization,the radiator works at operating frequency of 10MHzwith S11 value of -29.79dB and S21 value of -1.62dB. Whilstfrom experimental characterization, the operating frequency offabricated radiator is 9.21MHz with values of S11 and S21 of-20.22dB and -2.72dB, respectively.